Governance - Nickel, Rainer (EUNOMÍA. Revista en Cultura de la Legalidad, 2014)
Governance is a bridge term. It connects a perspective from political sciences - Governance as an advanced theory of governing and regulating – and a perspective from legal science - Governance by and through regulatory structures. It represents a structural change in the execution of public power, not in the sense of a decline, but in the sense of a change in the mode. In this regard Governance broadens the spectrum of regulatory structures without replacing traditional ways of governing; it is a complimentary technique which exists parallel to the traditional techniques of top-down administration and regulation. The turn to governance in law and politics raises serious concerns: about trends towards a de-formalization of law, about a growing de-politicization of law-making structures, and about a privatization of regulation that endangers the implementation of public goals.
Keywords: Governance; global governance; regulation; de-politicization; democracy